2023
DOI: 10.1161/circulationaha.122.062814
|View full text |Cite
|
Sign up to set email alerts
|

Exercise for the Prevention of Anthracycline-Induced Functional Disability and Cardiac Dysfunction: The BREXIT Study

Abstract: Background: Breast cancer (BC) survivors treated with anthracycline-based chemotherapy (AC) have increased risk of functional limitation and cardiac dysfunction. We conducted a 12-month randomized controlled trial in 104 early-stage BC patients scheduled for AC to determine if 12-months of exercise training (ExT) could attenuate functional disability (primary endpoint), improve cardiorespiratory fitness (VO 2 peak) and prevent cardiac dysfunction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
64
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(82 citation statements)
references
References 45 publications
8
64
0
Order By: Relevance
“…Further, dietary modification (in accordance with established cardiovascular disease prevention nutrition guidelines [53][54][55] ) is an effective strategy for improving traditional cardiovascular risk and body composition profile, and when combined with exercise, may enhance its beneficial effects on cardiac function and VO 2peak . Notably, exercise training and nutritional counselling constitute core components of cardiovascular rehabilitation for individuals with established CVD 46,47,[55][56][57][58][59] , and our group recently demonstrated the utility of combined aerobic and resistance exercise in improving VO 2peak and cardiac reserve (via increased SV reserve) among anthracycline-treated breast cancer patients 60 . Taken together, there is strong theoretical rationale for further investigation into the therapeutic utility of exercise training, nutritional counselling and/or cardioprotective pharmacotherapy to improve VO 2peak , cardiac reserve and body composition profile among allo-SCT survivors.…”
Section: Blood-based Metabolic Risk Profilementioning
confidence: 99%
“…Further, dietary modification (in accordance with established cardiovascular disease prevention nutrition guidelines [53][54][55] ) is an effective strategy for improving traditional cardiovascular risk and body composition profile, and when combined with exercise, may enhance its beneficial effects on cardiac function and VO 2peak . Notably, exercise training and nutritional counselling constitute core components of cardiovascular rehabilitation for individuals with established CVD 46,47,[55][56][57][58][59] , and our group recently demonstrated the utility of combined aerobic and resistance exercise in improving VO 2peak and cardiac reserve (via increased SV reserve) among anthracycline-treated breast cancer patients 60 . Taken together, there is strong theoretical rationale for further investigation into the therapeutic utility of exercise training, nutritional counselling and/or cardioprotective pharmacotherapy to improve VO 2peak , cardiac reserve and body composition profile among allo-SCT survivors.…”
Section: Blood-based Metabolic Risk Profilementioning
confidence: 99%
“…While absolute changes of the two studies that assessed GLS at baseline and AC-end are similar to our measurements, 35,37 no information was given on overall PA of the included patients. Although Peck et al analysed the relationship between MVPA and GLS and reported a significant association, 20 the authors relied on self-reported measures which are likely to overestimate time spend at moderate to vigorous intensities.…”
Section: Discussionmentioning
confidence: 51%
“…A recent study by Foulkes et al in 104 breast cancer patients (mean age 51 years) undergoing AC compared cardiac markers of systolic function and biomarkers of myocardial injury between an exercise and usual care group. 35 ET consisted of 3 weekly 30-60 min aerobic exercise sessions at moderate to high intensity, combined with resistance training over 12 weeks. In their study, GLS deteriorated by 1.3% in the exercise group compared to 1.0% in the usual care group with no differences between the groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 This issue of Circulation features 2 studies that examine the potential benefit of performing physical activity during receipt of anthracycline-based chemotherapy for breast cancer. In one randomized clinical trial, Foul-kes et al 5 examined the usefulness of a 12-month exercise intervention in preserving exercise capacity among women with breast cancer receiving anthracycline-based chemotherapy. A total of 104 participants were randomized to either usual care, which consisted of encouragement and referral to written recommendations for physical activity, or an individualized multicomponent exercise program consisting of endurance, tempo, and both high-intensity interval and resistance training.…”
Section: Articles See P 532 and P 614mentioning
confidence: 99%